The information value of the stress test and bank opacity - Stavros Peristian; Donald P. Morgan; Vanessa Savino (Federal Reserve Bank of New York, 2010)
We investigate whether the 'stress test,' the extraordinary examination of the nineteen largest U.S. bank holding companies conducted by federal bank supervisors in 2009, produced information demanded by the market. Using standard event study techniques, we find that the market had largely deciphered on its own which banks would have capital gaps before the stress test results were revealed, but that the market was informed by the size of the gap; given our proxy for the expected gap, banks with larger capital gaps experienced more negative abnormal returns. Our findings suggest that the stress test helped quell the financial panic by producing vital information about banks. Our findings also contribute to the academic literature on bank opacity and the value of government monitoring of banks.
Keywords: G01; G21; 330; Supervisory capital assessment program; capital gap; event study